Energetic analysis of reheating furnaces in the combustion of coke oven gas, Linz-Donawitz gas and blast furnace gas in the steel industry - Mariños Rosado, Diego J. [UNESP]; Rojas Chávez, Samir B. [UNESP]; Amaro Gutierrez, Jordan [UNESP]; Mayworm de Araújo, Fernando H. [UNESP]; de Carvalho, João A. [UNESP]; Mendiburu, Andrés Z. (Elsevier, 2020)
The reheating furnace of the steel industry was evaluated in the present study, which uses the gas mixture from coke oven (COG), steelmaking process “Linz-Donawitz” (LDG) and blast furnace (BFG); with the production of steel laminates being its main activity. Two methods were developed in this work to deal with energy consumption. The first dealt with improved estimation of heat losses in the furnace, and the second dealt with recovery of heat and its use in load preheating and combustion air preheating. These evaluations were intended to determine the best selection of material for insulation of the furnace, in order to increase heat transfer, to obtain an economy in fuel consumption, and to improve technical energy indicators of production and heat generation, as well as to improve the efficiency of the furnace and the combustion process. When developing the present study in the reheating furnace it was evidenced an economy in the fuel consumption of the COG/LDG mixture of 6606 m3/h and 4627 m3/h for the load preheating and the air preheating, respectively. In addition, efficiency of the furnace was increased by 23.3% and 15.2%, with the technical energy indicators improved by 18.9% and 13.2% in each case. For the COG/BFG mixture, the results obtained were similar.
Keywords: Combustion air preheating; Energy consumption; Heat recovery; Load preheating; Reheating furnace; Steel industry